The new Internal Transcribed Spacer 2 diagnostic tool clarifies the taxonomic position and geographic distribution of the North American malaria vector Anopheles punctipennis - Hodge, James M. (Malar J, 2021)
BACKGROUND: The malaria mosquito Anopheles punctipennis, a widely distributed species in North America, is capable of transmitting human malaria and is actively involved in the transmission of the ungulate malaria parasite Plasmodium odocoilei. However, molecular diagnostic tools based on Internal Transcribed Spacer 2 (ITS2) of ribosomal DNA are lacking for this species. Anopheles punctipennis is a former member of the Anopheles maculipennis complex but its systematic position remains unclear. METHODS: In this study, ITS2 sequences were obtained from 276 An. punctipennis specimens collected in the eastern and midwestern United States and a simple and robust Restriction Fragment Length Polymorphism approach for species identification was developed. The maximum-likelihood phylogenetic tree was constructed based on ITS2 sequences available through this study and from GenBank for 20 species of Anopheles. RESULTS: The analysis demonstrated a consistent ITS2 sequence length and showed no indications of intragenomic variation among the samples based on ITS2, suggesting that An. punctipennis represents a single species in the studied geographic locations. In this study, An. punctipennis was found in urban, rural, and forest settings, suggesting its potential broad role in pathogen transmission. Phylogeny based on ITS2 sequence comparison demonstrated the close relationship of this species with other members of the Maculipennis group. CONCLUSIONS: This study developed molecular tools based on ITS2 sequences for the malaria vector An. punctipennis and clarified the phylogenetic position of the species within the Maculipennis group.